Exploration and Identification of Ectomycorrhizal Fungi at IPB University Campus Forest - Adilah Adawiah; Dinda Rista Mufidah; Ivan Permana Putra (UIN Sunan Gunung Djati Bandung, 2023)
The exploration of ectomycorrhizal fungi diversity around the campus could provide insights into the presence and distribution of these symbiotic fungi in the area. This study aimed to observe, identify, and provide information regarding ectomycorrhizal fungi diversity in the IPB University Campus Forest. The sampling sites represent various tree species including forests, parks, and green spaces. The exploration was done using opportunistic sampling method. The obtained basidiomata were examined for macromorphological and micromorphological examination to identify the ectomycorrhizal fungi. The identification results based on the morphological characteristics confirmed our specimens as Inocybe cf. squarrosolutea (Corner & E. Horak) Garrido and Suillus bovinus (L.) Roussel. The Inocybe was characterized by having small to medium-sized, pileus squamules, dry surface, light brown to yellowish cap, lamellae crowded, cylindrical or attenuated stipe towards the apex, clavate basidia, and hemispheric knobs basidiospores. The Suillus was distinguished by having a cap that is convex in shape with a slightly brownish yellow color and the surface texture of the cap is smooth, lamella in the form of pores that are quite large and angular, brownish yellow in color, yellow tubular stipe, clavate basidia, and oval spores. These two macrofungi are new records in the sampling area and I. cf. squarrosolutea could be the new information for Indonesia. Our finding provides valuable information for ecological studies and contributes to the additional data on Indonesian ectomycorrhizal fungi diversity.